Impact of Differing Electron and Ion Temperatures on Emission Lines of Impurities in Tokamak Divertors. Issue 4 (June 2014) - Koubiti, M.; Godbert‐Mouret, L.; Ferri, S.; Marandet, Y.; Rosato, J.; Stamm, R.
Abstract In this paper we present some investigations of the broadening mechanisms affecting the emission line profiles of impurities present in the divertor regions of tokamaks. For that purpose, we have considered two visible lines (C IV n = 5‐6 and n = 6‐7) emitted by lithium‐like carbon ions for which the contributions of the Zeeman, Stark and Doppler effects are examined. The paper is focused on the impact of differing electron and ion temperatures on the broadening and shapes of the C IV n = 6‐7 line for conditions relevant to a detached tokamak divertor plasma. It is shown, that the C IV n = 6‐7 line profile calculated with differing electron and ion temperatures may be significantly different from the one calculated with equal temperatures but the same density. This suggests that the electron density determination from the fit of the measured spectra of such a line may be inaccurate when using equal ion and electron temperatures instead of differing ones. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)